ANALISIS HUKUM DAN ETIKA TERHADAP TANGGUNG JAWAB PERS INDONESIA DALAM PEMBERITAAN PERS YANG DAPAT MEMICU KONFLIK DI MASYARAKAT - AL FARISI, SALMAN (Dinamika Hukum, 2018)
The result of the research that the press coverage that can trigger the conflict in the community can be concluded that: the news that can trigger the conflict in society is through the right of reply (Article 5 paragraph [2] Act of Press) and right of correction (Article 5 paragraph [3] . The right of reply is the right of a person or a group of people to respond or refute to the news in the form of facts that are detrimental to his good name, while the right of correction is the right of everyone to correct or correct misinformation provided by the press, both about himself and others. Article 10 of the Regulation of the Press Council Number: 6 / Regulation-DP / V / 2008 concerning Ratification of Decree of the Press Council Number 03 / SK-DP / III / 2006 on Journalistic Code of Ethics as a Press Council Regulation (